Exploration of Business Actors' Strategies in Utilizing Paid Advertising to Increase Online Sales - Patricia Jeaneth Cyntia Kojongian; Erna Ngala; Treesje Imran (Oikonomia : Journal of Management Economics and Accounting, 2025)
This research aims to explore the strategies employed by businesses in utilizing paid advertising to increase online sales. Amid the rapid development of technology and the digitalization of commerce, paid advertising has become one of the important elements in digital marketing strategies. Platforms such as Google Ads, Facebook Ads, Instagram Ads, and TikTok Ads allow businesses to reach target markets more specifically, quickly, and measurably. Through a qualitative approach with a case study method, this research analyzes the strategies used by businesses from various sectors, ranging from micro, small, and medium enterprises (MSMEs) to large-scale e-commerce companies. Data was collected through in-depth interviews with business owners who actively use paid digital advertising, as well as observations of their ad campaign performance. The results show that successful strategies generally involve a deep understanding of digital consumer behavior, clear determination of advertising objectives, selection of relevant advertising platforms, and utilization of analytics features for evaluation and optimization. In addition, proportionate ad budget allocation and engaging ad content also proved to be key factors in increasing sales conversion rates. This research contributes to the digital marketing literature and can serve as a practical reference for businesses looking to optimize the use of paid advertising to drive their online sales growth